(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The present study investigates the uptake and execution of reverse logistics within the automotive parts sector in Thailand. The study utilized a quantitative research methodology and gathered data from a sample of 150 participants representing various levels of the industry. The results suggest that primary parts suppliers possess a well-defined strategy and comprehension of the significance of reverse logistics within their business activities. Nonetheless, manufacturers belonging to the second and third tiers, which encompass small and medium-sized enterprises, exhibit a deficiency in their uptake and comprehension of recycling practices. This can be attributed to inadequate legal and policy backing from the government, outdated recycling technology, and elevated operational expenses. The research proposes that the government should offer incentives to the auto parts industry to implement eco-friendly practices, ensure compliance with regulations, extend financial assistance for eco-friendly design and production, allocate resources towards logistics technology, and provide tax benefits. The objective of these recommendations is to promote the implementation of reverse logistics as a means to decrease manufacturing expenses, enhance marketability, and advance ecological preservation. Potential avenues for further investigation may include an examination of the competitive benefits associated with the implementation of reverse logistics management and the adoption of environmentally sustainable practices within the context of the automotive parts sector in Thailand.